Analytical developments of p‐hydroxy prenylamine reference material for dope control research: Characterization and purity assessment. Issue 2 (26th October 2021) - Joseph, Athira; Kumar, Gangasani Jagadeesh; Pawar, Sachin Dattram; Hirlekar, Bhakti Umesh; Bharatam, Prasad V.; Konda, Satyanand; Mudiam, Mohana Krishna Reddy; Murty, Upadhyayula Suryanarayana; Sahu, P. L.; Dubey, Sachin; Radhakrishnanand, P.; Adye, Daya Raju; et al.
Abstract: Prenylamine was initially used for the treatment of angina pectoris and later on withdrawn from the market in 1988 due to cardiac arrhythmias concern. The major phase I metabolite of prenylamine is p ‐hydroxy prenylamine that has a chiral center in the structure. Even though p ‐hydroxy prenylamine was synthesized earlier, it lacked complete analytical developments for chiral high‐performance liquid chromatography (HPLC) separation. However, p ‐hydroxy prenylamine reference material is not commercially available. The innovation of this manuscript is the development and validation of a chiral HPLC separation method and more extensive characterization of the reference material than previously reported method. Therefore, it was hypothesized to develop and validate normal phase HPLC method for p ‐hydroxy prenylamine reference material. p ‐Hydroxy prenylamine was synthesized in two batches and characterized successfully using 13 C NMR, 1 H NMR, high‐resolution mass spectrometry (HRMS), Fourier transform infrared spectroscopy (FT‐IR), and thermogravimetric analysis (TGA). A normal phase chiral HPLC method was developed to analyze the p ‐hydroxy prenylamine purity. Separation of the p ‐hydroxy prenylamine enantiomers were achieved using ultra‐high‐performance liquid chromatography (UHPLC) on a ChiralCel ODH column at wavelength of 220 nm. The developed method was validated in terms of its linearity, accuracy, precision, and robustness for purification, purity assessment, and stability studies. Proton and carbon peaks were confirmed by nuclear magnetic resonance (NMR) analysis. Functional groups were confirmed by FT‐IR. Loss on drying was 0.3% and 0.6% for Batches 1 and 2, respectively. The purity of the developed reference material for Batches 1 and 2 was found to be 99.59% and 100%, respectively. Therefore, the synthesized batches of p ‐hydroxy prenylamine can be used in dope testing as reference material. Abstract : p ‐hydroxy prenylamine reference material is not available commercially. Even though p ‐hydroxy prenylamine was synthesized earlier, it lacked complete analytical developments for chiral high‐performance liquid chromatography (HPLC) separation. Therefore, p ‐hydroxy prenylamine reference material was synthesized in two batches and characterized by established analytical techniques along with purity and potency assessments.